The Southern Appalachian region a survey. - Ford, Thomas R., 1923-; Vance, Rupert B., 1899-1975 (University of Kentucky Press, 1962)
The Southern Appalachian Region is the largest American ""problem area""--An area whose participation in the economic growth of the nation has not been sufficient to relieve the chronic poverty of its people. The existence of the problem was recognized a generation ago, but in the past decade the resistance of such areas to economic advance has acquired a more urgent significance in American thought. In 1958, a group of scholars undertook to make a new survey of the Southern Appalachian Region. Aided by grants from the Ford Foundation ultimately amounting to 250,000, they set out to analyze t